Insights on the use and consequences of user-generated content in the context of portuguese luxury hotels - Caetano, Ana Rita Amaral (2018)
Facebook have captured a special interest from private users and business organizations. In parallel, the concept of user-generated content has appeared as an active marketing tool since Facebook users could spread the word and share opinions on their pages with their "so-called" Facebook friends. This study aims to identify and understand the strategies and purposes of luxury hotel brand followers on Facebook towards user-generated content. 355 user-generated posts from 50 valid hotel’s brand pages have been collected from Facebook and coded manually for each variable. Moreover, posts were treated as a respondent and were coded according several variables such gender, nationality, post type, etc. To get better results, a descriptive analysis was performed. The results showed that pots with images were the most chosen post type to share any type of content and the favorite content types were sharing moments from holidays and writing guest reviews. As to the best day to post content, each gender has its own preferences: for females are the weekends while males favor Wednesdays and Fridays. However, 83,4% of the brand pages did not engage with generated posts and the involvement only occurred with guest reviews and holidays’ moments. The results give insight about the strategies adopted by Facebook users to generate content on their profiles about a specific hotel brand and begin to fill the gap on user-generated content utilization by hotel managers.